Ways and Means for Managing Up: 50 Strategies for Helping You and Your Boss Succeed - Smullen, F. William (McGraw-Hill Education, 2014)
-- -- -- -- -- Ways and Means for Managing Up.
Electronic book
Keywords: Supervision of employees; Interpersonal relations; Management; Personnel; Supervision; Gestion; management